Wavelength conversion in WDM networking. - Ramamurthy, B.
Wavelength conversion has been proposed for use in wavelength-division multiplexed networks to improve efficiency. This study highlights systems challenges and performance issues which need to be addressed in order to incorporate wavelength conversion effectively. A review/survey of the enabling technologies, design methods, and analytical models used in wavelength-convertible networks is provided
Keywords: WDM networking; Analytical models; Design methods; Efficiency; Management algorithms; Optoelectronic devices; Performance; Review/survey.; Routing algorithms; Wavelength conversion; Wavelength-convertible networks; Wavelength-division multiplexed networks; Wavelength-routed network design